+0  
 
+1
50
2
avatar

(x^(3/2))^(1/6)

___________

(x^(2/3))^(1/6)

 

simplify and use only positive exponents

Guest Sep 18, 2017
Sort: 

2+0 Answers

 #1
avatar+7055 
0

(x^(3/2))^(1/6)

___________

(x^(2/3))^(1/6)

simplify and use only positive exponents

 

\((x^\frac{3}{2})^\frac{1}{6}/(x^\frac{2}{3})^\frac{1}{6} \)

\(=x^\frac{1}{4}/x^\frac{1}{9}\\ =x^{\frac{1}{4}-\frac{1}{9}}\\ \color{blue}=x^{\frac{5}{36}}\) 

 

laugh  !

asinus  Sep 18, 2017
 #2
avatar+18601 
0

(x^(3/2))^(1/6)

___________

(x^(2/3))^(1/6)

 

simplify and use only positive exponents

 

\(\begin{array}{|rcll|} \hline && \dfrac{ (x^{\frac{3}{2}} )^{ \frac{1}{6} } } { (x^{\frac{2}{3}})^{ \frac{1}{6} } } \\ &=& \left(\dfrac{ x^{\frac{3}{2}} } { x^{\frac{2}{3}} } \right)^{ \frac{1}{6} } \\ &=& \left(x^{\frac{3}{2}} \cdot x^{-\frac{2}{3}} \right)^{ \frac{1}{6} } \\ &=& \left(x^{\frac{3}{2}-\frac{2}{3}} \right)^{ \frac{1}{6} } \\ &=& \left(x^{\frac{9-4}{6}} \right)^{ \frac{1}{6} } \\ &=& \left(x^{\frac{5}{6}} \right)^{ \frac{1}{6} } \\ &=& x^{\frac{5}{6}\cdot\frac{1}{6} } \\ &=& x^{\frac{5}{36}} \\ \hline \end{array} \)

 

laugh

heureka  Sep 19, 2017

12 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details